Non-contractual obligations in private international law: comparative-legal analysis - Kudryavtseva L. V., Samsonov S. A. (Interactive science, 2017)
using a comparative law method this article describes the similarities and differences in the obligations as a result of the injury in the Russian Federation and other countries of continental legal family, characterizes the responsibility for harm caused by deficiencies of goods, jobs and services under the laws of the countries in the Anglo-Saxon legal family. The work also suggests the ways to improve the legislation.
Keywords: моральный вред; международное частное право; обязательства вследствие причинения вреда; зарубежное законодательство; ответственность за вред; недостатки товаров; недостатки работ; недостатки услуг; obligations as a consequence of injury; international private law; moral damage; foreign law; liability for damage; deficiencies of goods; deficiencies of jobs; deficiencies of services